Comparison between single incision laparoscopic cholecystectomy using conventional laparoscopic instruments vs. four port laparoscopic cholecystectomy in patients of symptomatic cholelithiasis: a prospective randomised study - Gupta, Archit; Gupta, Jagdish K.; Jhobta, R. S.; Mahajan, Anjali (International Surgery Journal, 2023)
Background: The desire to reduce invasiveness, pain, discomfort and improve cosmesis and early return of patient to normal activities is the basis for single incision laparoscopic surgery. The primary aim was to compare post-operative pain and the secondary aim to compare duration of surgery, intraoperative bile spill or stone spill, duration of hospital stay, any postoperative complications and cosmetic outcome between SILC and the gold standard for symptomatic gall stone disease, FPLC (Four port laparoscopic cholecystectomy). Methods: A total of 150 patients were randomized into two groups, A (SILC) and B (FPLC). Post-operative pain and other intra-operative and post -operative parameters were compared. Results: The age ranged between 20 years to 76 years most of them being females with body mass index ranging between 19 and 35 kg/m2. Comparison of pain score was done using MEWS scale; which was found to be statistically significantly SILC at 6 hours, mean difference (MD)-0.833 while at 24 hours the difference was not significant (MD- 0.234). Duration of surgery was significantly more (MD-12.17 minutes) in SILC. No addition of port or conversion to open cholecystectomy was required. There were no significant difference between post-operative complications between the two groups. Cosmesis was significantly better in terms of look of the scar (MD-0.867) and recommending it to their relatives (MD-0.700) in SILC group. Conclusions: SILC is a safe and easily learnable procedure which can be safely be done using conventional laparoscopic instruments in low risk patients. Duration of surgery even after expertise is gained remains to be more than FPLC.